Functional outcomes of adolescents with a history of specific language impairment (SLI) with and without autistic symptomatology - Durkin, K.; Conti-Ramsden, Gina; Simkin, Z. (Springer New York LLC, 2012)
This study investigates whether the level of language ability and presence of autistic symptomatology in adolescents with a history of SLI is associated with differences in the pattern of difficulties across a number of areas of later functioning. Fifty-two adolescents with a history of SLI participated. At age 14, 26 participants had a history of SLI but no autistic symptomatology and 26 had a history of SLI and autistic symptomatology. At age 16, outcomes were assessed in the areas of friendships, independence, academic achievement, emotional health and early work experience for both subgroups and for 85 typically developing peers. Autistic symptomatology was a strong predictor of outcomes in friendships, independence and early work experience whilst language was a strong predictor of academic achievement. No significant associations were found for later emotional health.